2010
DOI: 10.1186/1471-2105-11-s7-s10
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and verification of the HMGB1 signaling pathway

Abstract: BackgroundRecent studies have found that overexpression of the High-mobility group box-1 (HMGB1) protein, in conjunction with its receptors for advanced glycation end products (RAGEs) and toll-like receptors (TLRs), is associated with proliferation of various cancer types, including that of the breast and pancreatic.ResultsWe have developed a rule-based model of crosstalk between the HMGB1 signaling pathway and other key cancer signaling pathways. The model has been simulated using both ordinary differential e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 62 publications
(76 reference statements)
1
64
0
1
Order By: Relevance
“…In fact, we have recently applied both approaches to verify computational models of biological signaling pathways [20] and analog circuits [47]. In the systems biology application, models are inherently probabilistic because of the stochastic nature of the (quantum) physics underlying chemical reactions.…”
Section: Experimental Results In Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, we have recently applied both approaches to verify computational models of biological signaling pathways [20] and analog circuits [47]. In the systems biology application, models are inherently probabilistic because of the stochastic nature of the (quantum) physics underlying chemical reactions.…”
Section: Experimental Results In Applicationmentioning
confidence: 99%
“…In particular, the pioneering work of Gillespie [19] showed that, under some reasonable assumptions, one can use continuous-time Markov chains to approximate the temporal evolution of chemical reaction networks. In our work [20] we used the BioNetGen rule-based language [26] to succinctly describe the reactions of an important signaling pathway in cancer. The model (i.e., the resulting continuous-time Markov chain) is then efficiently simulated by the BioNetGen simulator and verified against known behavioral properties expressed in BLTL.…”
Section: Experimental Results In Applicationmentioning
confidence: 99%
“…Bioinformatic analysis has even revealed that overexpressed HMGB1 can influence cell fate, such as apoptosis or proliferation, through regulation of cell circle factors, including c-Myc, p53, pRb, Ras, etc. (79). The possibility of intracellular gHMGB1-mediated neuronal apoptosis may be caused by aberrant expression of these cell circle factors.…”
Section: Discussionmentioning
confidence: 99%
“…Au ß erdem bestehen Querverbindungen zu p53-MDM [61] , Rho-GTPasen [62] , Jak/STAT [63] und Mac-152 zudem spielt RAGE eine wichtige Rolle in der DNAabh ä ngigen Aktivierung von TLR9, sodass RAGE weniger als konventioneller Rezeptor sondern viel mehr als Adapter f ü r verschiedenste Signalwege gesehen werden kann [34] . HMGB1 aktiviert ü ber Bindung an RAGE dendritische Zellen und f ö rdert ihre Reifung, was zur Aussch ü ttung von proinflammatorischen Zytokinen wie IL-1-α , IL-6 und TNF-α f ü hrt.…”
Section: Funktionen Von Hmgb1 Und Rageunclassified